Religiolinguistic Authority and Digital Hybridity: Arabic and Sasak Language Contestation Among Mataram Muslim Communities on Social Media Platforms - Sultan Sultan; Bambang Prastio (CV. Creative Tugu Pena, 2026)
This study explores the complex dynamics of Arabic and Sasak language contestation within religiolinguistic practices of the Mataram Muslim community across digital platforms. Employing a netnographic methodology grounded in interpretive-constructivist epistemology, this research examines how language choices function as markers of religious authority, cultural identity, and social positioning in online religious discourse. Data were collected from six digital platforms over twelve months, generating a corpus of 2,847 posts and 15,324 comments. Through thematic analysis, critical discourse analysis, and semiotic interpretation, this study reveals three major patterns: (1) language stratification whereby Arabic language accumulates religious authority while Sasak language signifies local legitimacy and accessibility; (2) creative hybridity and strategic code-switching as mechanisms through which communities actively negotiate linguistic power relations; and (3) implicit contestation wherein community members resist linguistic hierarchization through subtle rhetorical strategies. Theoretically, this research advances understanding of how Muslim communities perform postcolonial religiolinguistic identity within algorithmically mediated spaces. Practically, findings underscore the importance of culturally responsive approaches to digital religiosity, with implications for Islamic education, content creation, and digital literacy. This research contributes to closing the gap in scholarly literature regarding how Southeast Asian Muslim communities authentically construct and transform religious identity through linguistically mediated digital practices.